2010
DOI: 10.1093/ejechocard/jeq027
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive organic mitral regurgitation associated with benfluorex therapy

Abstract: Although it cannot affirm a definitive causal relationship, the present study strongly suggests that patients treated with benfluorex might incur a risk of restrictive organic valvular heart disease. Therefore, echocardiography should be performed in patients exposed to benfluorex in case of occurrence of symptoms or signs of valvular disease. Further data are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
2
8
0
3
Order By: Relevance
“…This finding was confirmed by another case-control study showing that among patients with mitral regurgitation of unclear origin, exposure to benfluorex was identified in 40.9% of cases compared with 4.5% in a matched group of patients with degenerative mitral regurgitation resulting from flail leaflets. 9 These series of observations were followed by retrospective cohort studies estimating of the risk of valvular damage, hospitalizations, valve surgery, and death associated with benfluorex exposure. 10,11 The first cohort study by Weill et al 10 used the database of the French National System of Reimbursement Information (Système national d'information inter régime de l'assurance maladie) and discharge diagnostic data from public and private hospitalizations (Programme de médicalisation des systèmes d'informations) and analyzed diabetic patients 40 to 69 years of age with reimbursements for antidiabetic drugs in 2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was confirmed by another case-control study showing that among patients with mitral regurgitation of unclear origin, exposure to benfluorex was identified in 40.9% of cases compared with 4.5% in a matched group of patients with degenerative mitral regurgitation resulting from flail leaflets. 9 These series of observations were followed by retrospective cohort studies estimating of the risk of valvular damage, hospitalizations, valve surgery, and death associated with benfluorex exposure. 10,11 The first cohort study by Weill et al 10 used the database of the French National System of Reimbursement Information (Système national d'information inter régime de l'assurance maladie) and discharge diagnostic data from public and private hospitalizations (Programme de médicalisation des systèmes d'informations) and analyzed diabetic patients 40 to 69 years of age with reimbursements for antidiabetic drugs in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…7 Moreover, 2 case-control studies have reported an important proportion of benfluorex use in patients admitted to hospital for severe organic mitral regurgitation of unclear origin. 8,9 In a retrospective cohort study of 2 French national databases including a large number of patients with diabetes mellitus, Weill et al 10 observed a 3-fold increase in the risk of hospitalization for valve regurgitation and a 4-fold increase in the risk of valve replacement surgery in patients exposed to benfluorex. According to recent estimations, exposure to benfluorex might have been responsible for up to 3100 admissions to hospital for valvular heart disease and up to 1300 deaths resulting from valve regurgitations in France.…”
mentioning
confidence: 99%
“…Le benfluorex expose à un risque de valvulopathie [12][13][14][15][16][17][18][19][20][21]. En effet, un ensemble de données récentes de la littérature comprenant des cas cliniques isolés [12][13][14][15], des séries d'observations [16,22], deux études « cas-témoin » [17,18], une étude randomisée [21] et deux grandes enquêtes de cohortes de la CNAM [19,20] établit que le benfluorex peut être à l'origine de lésions valvulaires cardiaques.…”
Section: Atteintes Valvulaires Et Benfluorexunclassified
“…Après ajustement sur l'IMC, la présence d'un diabète et la prise de dexfenfluramine, le benfluorex est apparu associé à un risque élevé d'insuffisance mitrale (risque relatif 17, intervalle de confiance à 95 % : 3,5 à 83, p < 0,01). Une deuxième étude de méthodologie proche réalisée en Picardie, avec de nouveau une recherche faite « en aveugle » d'une exposition au benfluorex, a confirmé les résultats initialement obtenus en Bretagne [18]. Dans ce travail rétrospectif réalisé sur la période 2003-2008, 22 patients hospitalisés dans le département de cardiologie du centre hospitalo-universitaire d'Amiens atteints d'une insuffisance mitrale restrictive d'étiologie inexpliquée (cas) ont été identifiés et appariés pour l'âge, le sexe, la taille, le poids et la présence d'un diabète, à 22 patients opérés pendant la même période d'une insuffisance mitrale dégénéra-tive par prolapsus (« témoins »).…”
Section: éTudes Cas-témoinunclassified
“…Une autre pièce a cependant été apportée au dossier de suspicion d'une relation entre benfluorex et valvulopathies sous la forme d'une étude cas-témoin rétrospective similaire sur une population de patients expressément référés dans un centre tertiaire pour l'évaluation d'une insuffisance mitrale organique entre 2003 et 2008 [54]. Les 22 cas étaient définis par la présence d'une régurgitation mitrale sur un méca-nisme restrictif dont l'origine était peu claire (10/22 de grade ≥ 3/4), et les 156 témoins étaient des sujets avec une régurgitation mitrale sur rupture de cordage, dont 22 ont été matchés pour le sexe, l'âge, le poids, la taille et la présence de diabète.…”
Section: Benfluorex Et Valvulopathiesunclassified